Warren Buffett stock portfolio - Buffett, Mary; Clark, David (London Simon & Schuster, 2012)
Presents an in-depth look at the stocks owned by Warren Buffett to explain why he has invested in them, sharing detailed case studies that reveal specific reasons each business has been declared good for long-term investments.
Unabridged.
"Includes bonus materials"--Container.
Compact discs.
Read by Marcia Strassman ; with an introduction by the author.
Keywords: Investments; Stocks; Audiobooks